Electron compound hydrogen storage material catalyst, hydrogen storage material containing catalyst and preparation method

Ti5Si3-based electronic compound catalysts address the kinetic issues in magnesium-based hydrogen storage by enhancing catalytic activity and stability, achieving efficient hydrogen absorption and desorption in a Ti5Si3-MgH2 composite.

CN119186542APending Publication Date: 2024-12-27CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411324941.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Magnesium-based hydrogen storage materials lack effective catalytic active sites, leading to poor hydrogen absorption and desorption kinetics, and the active anionic electronic properties of electronic compounds in these materials form strong transition metal-hydrogen bonds, increasing the activation energy of hydrogen diffusion.

Method used

The use of Ti5Si3 as an electronic compound catalyst, prepared by mixing Ti and Si powders, compacting, impurity removal, and smelting, followed by compounding with MgH2 through intermittent ball milling, to create a Ti5Si3-MgH2 composite hydrogen storage material.

Benefits of technology

Ti5Si3 provides high anionic electron activity for hydrogen adsorption and diffusion, achieving balanced dissociation and diffusion processes, with improved catalytic activity, releasing 5.28wt.% hydrogen at 300°C and maintaining 4.77wt.% capacity after 50 cycles, demonstrating high stability and suitability for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186542A_ABST
    Figure CN119186542A_ABST
Patent Text Reader

Abstract

The invention relates to an electronic compound hydrogen storage material catalyst, a hydrogen storage material containing the catalyst and a preparation method, and belongs to the technical field of hydrogen storage. The electronic compound is Ti5Si3, and has great advantages in the aspect of improving the magnesium-based hydrogen storage performance due to high catalytic activity. After the composite hydrogen storage material is compounded with MgH2, 5.28 wt% of hydrogen is released at the temperature of 300 DEG C for 5 min, 4.51 wt% of hydrogen is released at the temperature of 240 DEG C for 30 min, and the activation energy of the hydrogen release reaction is 70.4 kJ / mol; the hydrogen absorption amount of the composite hydrogen storage material is 4.07 wt.% at the temperature of 250 DEG C within 30 s, and the hydrogen absorption amount of the composite hydrogen storage material is 5.00 wt.% at the temperature of 250 DEG C within 7 min. In addition, after 50 times of hydrogen absorption and desorption cycles, the composite hydrogen storage material can still keep the hydrogen storage capacity of 4.77 wt.% or above. The catalyst has the advantages of good stability, simple preparation process and easily available raw materials, and is suitable for expanded production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen storage, and in particular relates to an electronic compound hydrogen storage material catalyst, a hydrogen storage material containing the catalyst, and a preparation method thereof. Background Art

[0002] In recent years, hydrogen energy has been proposed as a promising energy storage carrier due to its clean and high-density characteristics. By combining with electrolysis and hydrogenation reactions, it can store renewable energy in the form of hydrogen. At present, in the industrial chain of hydrogen production, storage, transportation, addition and use, hydrogen storage and transportation is the bottleneck link for large-scale hydrogen energy utilization. Although the existing high-pressure gaseous and low-temperature liquid hydrogen storage technologies are relatively mature, there are still problems such as harsh storage and transportation conditions, flammability, explosion and leakage. Solid-state hydrogen storage reduces the potential risk of hydrogen leakage due to the high stability of the chemical bond between metal and hydrogen, thereby improving the safety of hydrogen storage and transportation. Among many solid-state hydrogen storage materials, magnesium-based solid-state hydrogen storage materials have the advantages of high mass hydrogen storage density, reversible hydrogen absorption and desorption process, low price, and green environmental protection, which provides greater possibilities for large-scale solid-state hydrogen storage. However, magnesium-based hydrogen storage materials lack effective catalytic active sites, resulting in poor hydrogen absorption and desorption kinetics of the material. At present, adding catalysts is one of the effective methods to introduce catalytic active sites in magnesium-based hydrogen storage materials. Among them, effective control of catalyst-hydrogen interaction is the key to designing efficient catalysts.

[0003] In recent years, electronic compounds have received extensive attention in the field of catalytic hydrogenation due to their unique anionic electronic properties. However, in the field of magnesium-based hydrogen storage, the active anionic electronic properties of electronic compound materials are very effective in the hydrogen dissociation process, but they easily form strong transition metal-hydrogen chemical bonds, resulting in a significant increase in the activation energy of the hydrogen diffusion process. Therefore, how to balance the contradictory relationship between the hydrogen dissociation and hydrogen diffusion processes of electronic compound catalysts is the key to further improving the performance of magnesium-based hydrogen storage materials. Summary of the invention

[0004] In view of this, one of the objects of the present invention is to provide an electronic compound hydrogen storage material catalyst; the second object is to provide a method for preparing the electronic compound hydrogen storage material catalyst; the third object is to provide a hydrogen storage material containing the catalyst; and the fourth object is to provide a method for preparing the hydrogen storage material containing the catalyst.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] 1. An electronic compound hydrogen storage material catalyst, wherein the electronic compound is Ti5Si3.

[0007] 2. The preparation method of the electronic compound hydrogen storage material catalyst is as follows: Ti powder and Si powder are mixed and placed in a stamping die for compaction to obtain a mixed block, and the mixed block is subjected to impurity removal and then smelted.

[0008] Preferably, the molar ratio of the Ti powder to the Si powder is 5:3.

[0009] Preferably, the compacting is specifically: compacting the mixed powder in a stainless steel stamping die at a pressure of 15 to 20 MPa.

[0010] Preferably, the impurity removal treatment is specifically: placing the mixed block in a tube furnace, under the protection of inert gas, and heat treating it at 550-750° C. for 2-6 hours.

[0011] Preferably, the smelting is specifically: performing arc melting at least three times in a vacuum melting furnace.

[0012] 3. A Ti5Si3-MgH2 composite hydrogen storage material, which comprises, by mass percentage, 5-15 wt.% Ti5Si3 and 85-95 wt.% MgH2.

[0013] 4. A method for preparing a Ti5Si3-MgH2 composite hydrogen storage material, the preparation method being as follows: MgH2 and Ti5Si3 are intermittently ball-milled at a speed of 200 to 800 rpm for 8 to 12 hours at a ball-to-material ratio of 20 to 40:1 under an argon atmosphere.

[0014] Preferably, the forward and reverse intermittent ball milling is specifically as follows: after each ball milling for 8 to 12 minutes, pause for 8 to 12 minutes, and reverse for 8 to 12 minutes and pause for 8 to 12 minutes.

[0015] The beneficial effects of the present invention are as follows: the present invention provides an electronic compound hydrogen storage material catalyst, a hydrogen storage material containing the catalyst and a preparation method, the electronic compound is Ti5Si3, there are high concentrations of anionic electrons in the holes of the Ti5Si3 crystal structure, these anionic electrons not bound by atomic orbitals have excellent activity, so that Ti5Si3 can achieve good catalytic activity through electron transfer. Since Ti5Si3 has a suitable anionic electron energy band position, it is not only conducive to the adsorption and dissociation of hydrogen molecules by anionic electrons in Ti5Si3, but also conducive to the diffusion of hydrogen atoms, achieving a good match between hydrogen dissociation and diffusion processes, and thus having higher catalytic activity, and having great advantages in improving the performance of magnesium-based hydrogen storage. Specifically, after being compounded with MgH2, the composite hydrogen storage material releases 5.28wt.% of hydrogen at 300°C for 5 minutes, and releases 4.51wt.% of hydrogen at a lower temperature of 240°C for 30 minutes, and the activation energy of the hydrogen release reaction is 70.4kJ / mol; the composite hydrogen storage material absorbs 4.07wt.% of hydrogen at 250°C for 30 seconds, and 5.00wt.% of hydrogen at 250°C for 7 minutes. In addition, after 50 cycles of hydrogen absorption and desorption, the composite hydrogen storage material can still maintain a hydrogen storage capacity of more than 4.77wt.%. The catalyst has good stability, a simple production process, and readily available raw materials, and is suitable for large-scale production.

[0016] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0018] Figure 1 The XRD pattern of the electronic compound hydrogen storage material catalyst Ti5Si3 prepared in Example 1;

[0019] Figure 2 The SEM and energy spectrum of the electronic compound hydrogen storage material catalyst Ti5Si3 prepared in Example 1;

[0020] Figure 3 The graphs are the test results of the hydrogen release performance of the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 at 300°C, 280°C, 260°C and 240°C respectively;

[0021] Figure 4The graph is a test result of hydrogen absorption performance of the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 at 100°C, 150°C, 200°C, 250°C, and 3MPa;

[0022] Figure 5 This is a graph showing the test results of the cyclic hydrogen absorption and desorption performance of the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 at 280°C. DETAILED DESCRIPTION

[0023] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0024] Example 1

[0025] Preparation of electronic compound hydrogen storage material catalyst Ti5Si3

[0026] (1) Ti powder and Si powder were mixed at a molar ratio of 5:3, and then the mixed powder was compacted in a stainless steel stamping die at a pressure of 17.5 MPa to obtain a mixed block;

[0027] (2) placing the mixed block obtained in step (1) in a tube furnace, under argon protection, and heat treating at 650° C. for 4 h to remove moisture and impurity gases;

[0028] (3) arc melting the mixed block after the treatment in step (2) three times on a copper furnace using a non-consumable tungsten electrode to obtain an electronic compound hydrogen storage material catalyst Ti5Si3.

[0029] The electronic compound hydrogen storage material catalyst Ti5Si3 prepared in Example 1 was characterized by X-ray diffractometer. Figure 1 As shown by Figure 1 It can be seen that the characteristic diffraction peaks of Ti5Si3 and pure Ti5Si3 are completely consistent, indicating that the preparation is successful, and the heat treatment and mechanical grinding do not change the phase composition and structural characteristics of Ti5Si3, indicating that the electronic compound has relatively good mechanical and chemical stability.

[0030] The electronic compound hydrogen storage material catalyst Ti5Si3 prepared in Example 1 was characterized by scanning electron microscopy and X-ray energy dispersive spectrometer (SEM-EDS). Figure 2 As shown by Figure 2 It can be seen that the Ti and Si elements in Ti5Si3 are evenly distributed, and the electronic compound catalyst has a block structure.

[0031] Example 2

[0032] Preparation of electronic compound hydrogen storage material catalyst Ti5Si3

[0033] (1) Ti powder and Si powder were mixed at a molar ratio of 5:3, and then the mixed powder was compacted in a stainless steel stamping die at a pressure of 20 MPa to obtain a mixed block;

[0034] (2) placing the mixed block obtained in step (1) in a tube furnace, under argon protection, and heat treating at 550° C. for 6 h to remove moisture and impurity gases;

[0035] (3) arc melting the mixed block after the treatment in step (2) three times on a copper furnace using a non-consumable tungsten electrode to obtain an electronic compound hydrogen storage material catalyst Ti5Si3.

[0036] Example 3

[0037] Preparation of electronic compound hydrogen storage material catalyst Ti5Si3

[0038] (1) Ti powder and Si powder were mixed at a molar ratio of 5:3, and then the mixed powder was compacted in a stainless steel stamping die at a pressure of 15 MPa to obtain a mixed block;

[0039] (2) placing the mixed block obtained in step (1) in a tube furnace, under argon protection, and heat treating at 750° C. for 2 h to remove moisture and impurity gases;

[0040] (3) arc melting the mixed block after the treatment in step (2) three times on a copper furnace using a non-consumable tungsten electrode to obtain an electronic compound hydrogen storage material catalyst Ti5Si3.

[0041] Example 4

[0042] Preparation of composite hydrogen storage material (10wt.%Ti5Si3-MgH2)

[0043] In a vacuum glove box, MgH2 and the Ti5Si3 powder prepared in Example 1 were weighed and mixed at a mass ratio of 90:10, with a total mass of 4 g. The mixture was then poured into a ball mill, and the mill was run at a speed of 400 rpm for 10 min, followed by a 10 min break, and then a 10 min break at a ball-to-material ratio of 20:1 under a 0.2 MPa argon atmosphere. The mill was then run forward for 10 min, then reversed for 10 min, and then reversed for 10 min. The effective milling time was 12 h to obtain a composite hydrogen storage material (10 wt.% Ti5Si3+MgH2). Among them, 40 g of a small stainless steel ball with a diameter of 5 mm, 20 g of a medium stainless steel ball with a diameter of 8 mm, and 20 g of a large stainless steel ball with a diameter of 10 mm.

[0044] The hydrogen release performance of the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 was tested at 240-300°C using a high pressure gas adsorption and desorption instrument. The results are as follows: Figure 3 As shown in Table 1, Figure 3 As shown in Table 1, the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) releases 5.28wt.% hydrogen in 5 minutes at 300°C, and releases 4.51wt.% hydrogen in 30 minutes at a lower temperature of 240°C. The activation energy of the hydrogen release reaction is 70.4kJ / mol.

[0045] Table 1 Statistical table of hydrogen release performance test data of composite hydrogen storage material (10wt.%Ti5Si3-MgH2) at 300℃, 280℃, 260℃ and 240℃

[0046]

[0047] The hydrogen absorption performance of the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 was tested by a high-pressure gas adsorption-desorption instrument at 100°C, 150°C, 200°C, 250°C, and 3MPa. The results are as follows: Figure 4 As shown in Table 2, Figure 4 As shown in Table 2, the hydrogen absorption amount of the composite hydrogen storage material is 4.07wt.% within 30s at 250°C, and 5.00wt.% within 7min at 250°C, indicating that it has excellent rapid hydrogen absorption kinetics.

[0048] Table 2 Statistical table of hydrogen absorption performance test data of composite hydrogen storage material (10wt.%Ti5Si3-MgH2) at 250℃ and 3MPa

[0049]

[0050] The composite hydrogen storage material (10wt.% Ti5Si3-MgH2) prepared in Example 4 was subjected to 50 cycles of hydrogen absorption and desorption at 280°C using a high pressure gas absorption and desorption apparatus. Figure 5 As shown in Table 3, Figure 5 As shown in Table 3, the initial hydrogen storage capacity of the system is 5.57wt.%, and it remains at 4.77wt.% after the 50th cycle. The capacity retention rate is 86%. It can be seen that the composite hydrogen storage material (10wt.% Ti5Si3-MgH2) has excellent cyclic hydrogen absorption and desorption performance.

[0051] Table 3 Statistical table of test data of composite hydrogen storage material (10wt.%Ti5Si3-MgH2) at 280℃ for 50 cycles of hydrogen absorption and desorption

[0052] Hydrogen absorption 1st time 10th 30th 50th 1min 5.43wt.% 4.86wt.% 4.36wt.% 4.11wt.% 8min 5.54wt.% 5.08wt.% 4.69wt.% 4.55wt.% 15min 5.55wt.% 5.16wt.% 4.77wt.% 4.61wt.% Hydrogen release 1st time 10th 30th 50th 5min 4.05wt.% 3.87wt.% 3.75wt.% 3.81wt.% 10min 5.06wt.% 4.73wt.% 4.55wt.% 4.53wt.% 15min 5.48wt.% 5.08wt.% 4.79wt.% 4.72wt.%

[0053] Example 5

[0054] Preparation of composite hydrogen storage material (5wt.%Ti5Si3-MgH2)

[0055] In a vacuum glove box, MgH2 and the Ti5Si3 powder prepared in Example 1 were weighed and mixed at a mass ratio of 95:5, with a total mass of 4g, and then the mixture was poured into a ball mill, and the mill was operated at a speed of 200rpm for 12min forward and 12min rest at a ball-to-material ratio of 40:1 under a 0.2MPa argon atmosphere, and the effective ball milling time was 10h to obtain a composite hydrogen storage material (5wt.%Ti5Si3+MgH2). Among them, 80g of small stainless steel balls with a diameter of 5mm, 40g of medium stainless steel balls with a diameter of 8mm, and 40g of large stainless steel balls with a diameter of 10mm.

[0056] Example 6

[0057] Preparation of composite hydrogen storage material (15wt.%Ti5Si3-MgH2)

[0058] In a vacuum glove box, MgH2 and the Ti5Si3 powder prepared in Example 1 were weighed and mixed at a mass ratio of 85:15, with a total mass of 4 g, and then the mixture was poured into a ball mill, and the mill was run at a speed of 800 rpm for 8 min, followed by 8 min of rest, and then reversed for 8 min and rested for 8 min, with an effective milling time of 8 h, to obtain a composite hydrogen storage material (15wt.%Ti5Si3+MgH2). Among them, 60 g of small stainless steel balls with a diameter of 5 mm, 30 g of medium stainless steel balls with a diameter of 8 mm, and 30 g of large stainless steel balls with a diameter of 10 mm.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. An electronic compound hydrogen storage material catalyst, characterized in that: The electronic compound is Ti5Si3.

2. The method for preparing the electronic compound hydrogen storage material catalyst according to claim 1, characterized in that: The preparation method is as follows: Ti powder and Si powder are mixed and placed in a stamping die for compaction to obtain a mixed block, and the mixed block is subjected to impurity removal and then smelting.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the Ti powder to the Si powder is 5:

3.

4. The preparation method according to claim 2, characterized in that: The compaction is specifically as follows: compacting the mixed powder in a stainless steel stamping die at a pressure of 15 to 20 MPa.

5. The preparation method according to claim 2, characterized in that: The impurity removal treatment is specifically as follows: placing the mixed block in a tubular furnace, under the protection of inert gas, and heat treating it at 550-750° C. for 2-6 hours.

6. The preparation method according to claim 2, characterized in that: The smelting specifically comprises: performing arc melting at least three times in a vacuum melting furnace.

7. A Ti5Si3-MgH2 composite hydrogen storage material, characterized in that: Calculated by mass percentage, the composite hydrogen storage material includes: Ti5Si3 5-15wt.%, MgH2 85-95wt.%.

8. A method for preparing a Ti5Si3-MgH2 composite hydrogen storage material, characterized in that: The preparation method is as follows: MgH2 and Ti5Si3 are intermittently ball-milled for 8 to 12 hours at a rotation speed of 200 to 800 rpm in a ball-to-material ratio of 20 to 40:1 under an argon atmosphere.

9. The preparation method according to claim 8, characterized in that: The forward and reverse intermittent ball milling is specifically as follows: after each ball milling for 8 to 12 minutes, pause for 8 to 12 minutes; after each reverse milling for 8 to 12 minutes, pause for 8 to 12 minutes.